The use of information and communication technologies in patriotic education - Roman, Kamil (Journal of Education, Health and Sport, 2019)
The purpose of this article is to present the essence of patriotism in Polish educational realities. Based on the known definitions of education, the author also presents the division and classification of patriotic education in Poland. The purpose of this paper is to present the role played by modern media in shaping patriotic attitudes. The article presents practical solutions in the field of using modern technologies in patriotic education.